2005
DOI: 10.1007/s11120-005-1369-7
|View full text |Cite
|
Sign up to set email alerts
|

A bacteriophytochrome regulates the synthesis of LH4 complexesin Rhodopseudomonas palustris

Abstract: The non-sulphur purple bacterium Rhodopseudomonas palustris contains five pucAB genes for peripheral light-harvesting complexes. Bacteria grown under high-light conditions absorb at 800 and 850 nm but in low-light the 850 nm peak is almost absent and LH2 complexes are replaced by LH4. The genome contains six bacteriophytochromes (Bph). Bphs sense light in the red/far-red through a reversible Pr to Pfr transformation that controls gene expression. Bph3 (RPA1537) controls the expression of a cluster of photosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
59
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 30 publications
5
59
0
Order By: Relevance
“…palustris; Figure 2(M)) isolated from both PS agar deeps and PMS-containing Balch tubes. On PMS plates, these strains anaerobically produce large amounts of Bchl relative to carotenoids (ratio 1:1.7) where, as previously observed by Evans et al [45], the photosynthetic RC was the dominant complex with Bchl a peak maxima near 808 nm at absorbance values over four times those of the LHI peak at 878 nm (Figure 4(J)). The LHII peak appeared as a subtle shoulder to the left of LHI near 860 nm.…”
Section: Diversity Of Isolated Strainssupporting
confidence: 74%
“…palustris; Figure 2(M)) isolated from both PS agar deeps and PMS-containing Balch tubes. On PMS plates, these strains anaerobically produce large amounts of Bchl relative to carotenoids (ratio 1:1.7) where, as previously observed by Evans et al [45], the photosynthetic RC was the dominant complex with Bchl a peak maxima near 808 nm at absorbance values over four times those of the LHI peak at 878 nm (Figure 4(J)). The LHII peak appeared as a subtle shoulder to the left of LHI near 860 nm.…”
Section: Diversity Of Isolated Strainssupporting
confidence: 74%
“…We created in-frame deletion mutants of RpBphP2 or RpBphP3 and assayed LH4 expression in cells by measuring the ratio of whole-cell absorbance at 800 nm to absorbance at 860 nm. The LH4 complex predominates when this ratio is >1, and the LH2 complex predominates when the ratio is <1 (16,19). We found that deletion of either one of the RpBphP genes disrupted LH4 synthesis in response to low light intensity, similar to previous reports (7,8) (Fig.…”
Section: Resultssupporting
confidence: 91%
“…An increase in LH4 synthesis is seen in R. palustris cells grown in red light under semiaerobic conditions (7,16). This finding is consistent with the conclusion that under semiaerobic conditions, BV is synthesized and incorporated into RpBphPs, allowing them to respond to red light.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…In the PSU, LH2 complexes surround the LH1/RC complexes in a two-dimensional network, the size and composition of which is controlled by a range of environmental conditions, including oxygen tension, incident light intensity, and light quality (8)(9)(10). In the case of the most studied purple photosynthetic bacterium Rhodobacter sphaeroides, the LH complexes and RCs are only synthesized when the oxygen tension is below a critical value (11,12).…”
mentioning
confidence: 99%